2015
DOI: 10.5550/sgia.151101.en.005o
|View full text |Cite
|
Sign up to set email alerts
|

Use of Dietary Supplements Among Elite Athletes

Abstract: SUMMARYMany athletes use supplements in their diet as part of regular training or competition, thus enabling more intense training by encouraging faster recovery between workouts, minimizing interference caused by disease or injury and increasing competitive performance. These supplements, unlike medications, are not subject to rigorous efficiency and safety checks and tests. There is a risk with regard to those supplements which include positive doping test result as a consequence of presence of the prohibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…Compared to these results, this study shows a slightly higher frequency of supplementation (34.5% vs. 51.8%). The difference between the results of these two studies can be partly explained by the different methodology used in the data collection, the period in which consumption of FS was examined among athletes and the way the survey was done (Heikkinen et al 2011) Namely, the study conducted by Omeragic et al (2015) was analyzed data on the use of food supplements among athletes reported by them during the doping control, so the lower percentage of athletes who use food supplements can be explained by the fact that only supplements and medications used by athlete during the period of seven days prior to analysis were recorded in doping forms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to these results, this study shows a slightly higher frequency of supplementation (34.5% vs. 51.8%). The difference between the results of these two studies can be partly explained by the different methodology used in the data collection, the period in which consumption of FS was examined among athletes and the way the survey was done (Heikkinen et al 2011) Namely, the study conducted by Omeragic et al (2015) was analyzed data on the use of food supplements among athletes reported by them during the doping control, so the lower percentage of athletes who use food supplements can be explained by the fact that only supplements and medications used by athlete during the period of seven days prior to analysis were recorded in doping forms.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the results of studies examining the effects of non-steroidal anti-inflammatory drugs (NSAIDs) on performance in sport show that there is no unique evidence of the prophylactic effect of pre-training NSAIDs on muscle pain and inflammation caused by training (Foster et al 2014;Mauger et al 2014;Coombs et al 2015). Studies on the effects of paracetamol on performance in sports suggest that paracetamol could have positive effects on performance (Baylis et al 2001;Omeragic et al 2015;Park et al 2016) in sports, but the timing of drug administration and the magnitude of dose that can produce a potentially ergogenic effect are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Although many athletes supplement their diet with various nutritional products, their knowledge about ingredients and threshold amounts of each nutrient within the human body is not well known 1,8 . Such athletes might become positive for doping as well as could be subjected to health risks due to overdosing certain nutrients 9 . The composition and quality of most supplements are still doubtful, due to insufficient standards, regulations and laws behind them 1,10 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, consumer safety can't be fully guaranteed. However well-balanced diet and optimized training schedules ensure good performances during competing and training hours [21].…”
Section: Introductionmentioning
confidence: 99%
“…However, the abundancy of these supplements among opponents, always pressurizes clean athletes during competitions thus, they have to win games ghting against dopers [ 22]. Further, the excessive consumption of dietary supplements may cause critical side effects and interactions within the body which affect the wellbeing of an athlete [21].…”
Section: Introductionmentioning
confidence: 99%